2015
DOI: 10.1021/acs.jpcb.5b03034
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Small Solute Particles in Viscous Liquids: Cage Diffusion, a Result of Decoupling of Solute–Solvent Dynamics, Leads to Amplification of Solute Diffusion

Abstract: We study the diffusion of small solute particles through solvent by keeping the solute-solvent interaction repulsive and varying the solvent properties. The study involves computer simulations, development of a new model to describe diffusion of small solutes in a solvent, and also mode coupling theory (MCT) calculations. In a viscous solvent, a small solute diffuses via coupling to the solvent hydrodynamic modes and also through the transient cages formed by the solvent. The model developed can estimate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…In order to understand how slowing down of solvent dynamics, which leads to the decoupling, effects the solute motion, we study a set of systems where we vary the solvent mass. As observed earlier 11,25 with the increase in solvent mass the decoupling between the solute and the solvent dynamics increases as seen from the D 2 /D 1 values in Table 1. In these studies the solutesolvent interaction is kept moderately attractive (ǫ 12 =6).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…In order to understand how slowing down of solvent dynamics, which leads to the decoupling, effects the solute motion, we study a set of systems where we vary the solvent mass. As observed earlier 11,25 with the increase in solvent mass the decoupling between the solute and the solvent dynamics increases as seen from the D 2 /D 1 values in Table 1. In these studies the solutesolvent interaction is kept moderately attractive (ǫ 12 =6).…”
Section: Resultssupporting
confidence: 76%
“…In this study we work with a solute-solvent system where the solute size is chosen to be small so that the solute can explore the inter-solvent cage 11 . In earlier studies 2,3 it has been shown that for such small solute particles the non-Gaussian behaviour of the van Hove correlation function is due to decoupling in solute-solvent dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally unexpected, this result was attributed to nonspecific interactions with bystander macromolecules. The importance of the electrostatic contribution to small molecule diffusion in crowded environments has also been emphasized recently (Acharya et al 2015;Kekenes-Huskey et al 2016). The impressive size of the simulated MG cytoplasm allowed a statistically accurate calculation of macromolecule transport properties.…”
Section: Computational Models Of Diffusion In the Cytoplasmmentioning
confidence: 95%